2006
DOI: 10.1177/0361198106195100102
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Demographic and Unobserved Heterogeneity in Air Passengers’ Sensitivity to Service Attributes in Itinerary Choice

Abstract: Modeling passengers’ flight choice behavior is valuable to understanding the increasingly competitive airline market and predicting air travel demand. Standard and mixed-multinomial logit models of itinerary choice for business travel are estimated on the basis of a stated preference survey conducted in 2001. The results suggest that observed demographic- and trip-related differences are incorrectly manifested as unobserved heterogeneity in a random-coefficient mixed logit model that ignores the demographic- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…5 Congestion related delays have also been shown to influence travel decisions. For example, Warburg et al (2006) show that on-time performance is one of several important itinerary choice factors for airline passengers. In the roadway literature, Small (1982) shows that urban commuters change their schedule to avoid congested highways.…”
Section: Introductionmentioning
confidence: 99%
“…5 Congestion related delays have also been shown to influence travel decisions. For example, Warburg et al (2006) show that on-time performance is one of several important itinerary choice factors for airline passengers. In the roadway literature, Small (1982) shows that urban commuters change their schedule to avoid congested highways.…”
Section: Introductionmentioning
confidence: 99%
“…Educational level and marital status were demonstrated as influencing factors by some earlier work (Oyewole 2001;Tyrell et al 2001;Ong and Tan 2010). Not surprisingly, past studies (Tyrell et al 2001;Warburg et al 2006;Yang, Lu and Hsu 2014) found that income level and occupational status were significantly associated with passengers' airline, airport, or destination choices as a socio-economic or socio-demographic indicator.…”
Section: Introductionmentioning
confidence: 91%
“…The low-care business model purposes to Several other socio-economic, socio-demographic, alternative-specific, or destination attributes have been found to have an impact on passengers' airline or airport choice. Some prior studies (Oyewole 2001;Warburg, Bhat and Adler 2006) found that passengers' gender might have a significant impact on passengers' stated airline or airport preference. Further, other past research (Tyrell, Countryman, Hong and Cai 2001;Tsaur and Wu 2005) highlighted the significant association between several age groups and passengers' choice.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies present approaches for itinerary market share estimation across multiple dimensions using discrete choice modeling. From those, early models used a multinomial logit (MNL) approach 8,9,10,11 ; while more recent models also apply nested logit (NL) models 12,13 , mixed multinomial logit (MMNL) models 14 and other alternatives approaches 15,16 . The mentioned aggregate passenger-allocation studies can be classified with respect the type of data they are based on: revealed preference data (RP) or booking data; stated preferences (SP) data or survey data; and a combination of both.…”
Section: Literature Reviewmentioning
confidence: 99%